2003
DOI: 10.1105/tpc.011817
|View full text |Cite
|
Sign up to set email alerts
|

PAA1, a P-Type ATPase of Arabidopsis, Functions in Copper Transport in Chloroplasts

Abstract: Copper (Cu) is an essential trace element with important roles as a cofactor in many plant functions, including photosynthesis. However, free Cu ions can cause toxicity, necessitating precise Cu delivery systems. Relatively little is known about Cu transport in plant cells, and no components of the Cu transport machinery in chloroplasts have been identified previously. Cu transport into chloroplasts provides the cofactor for the stromal enzyme copper/zinc superoxide dismutase (Cu/ZnSOD) and for the thylakoid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
273
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(299 citation statements)
references
References 76 publications
19
273
1
3
Order By: Relevance
“…Cells were analyzed 16 h after transformation by confocal microscopy. be more oxidized [8]. We hypothesize that for optimal photosynthesis, the chloroplast needs to have a Cu delivery system that balances the activity of lumenal plastocyanin and stromal SOD enzymes under variable metal supply, ensuring that sufficient SOD activity is present to prevent oxidative damage if plastocyanin is present and PSI can be reduced (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were analyzed 16 h after transformation by confocal microscopy. be more oxidized [8]. We hypothesize that for optimal photosynthesis, the chloroplast needs to have a Cu delivery system that balances the activity of lumenal plastocyanin and stromal SOD enzymes under variable metal supply, ensuring that sufficient SOD activity is present to prevent oxidative damage if plastocyanin is present and PSI can be reduced (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and regulation of SOD isoforms in plants has been a topic of a number of studies, which showed that oxidative stress, light, and electron transport activity affect plastidic SOD isoform expression [3,8,20]. It was recently shown that Cu feeding dramatically affects the activity of FeS-OD and Cu/ZnSOD isoforms, whereas the activity of MnSOD is not affected by Cu availability [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper transporting P-type ATPases were identified in the cytoplasmic and thylakoid membrane of the cyanobacterium Synechococcus (Kanamaru et al, 1994;Phung et al, 1994), and a related protein, PAA1, was shown to be involved in Cu 21 transport in chloroplasts of Pisum (Shikanai et al, 2003). The N terminus of PAA1 targets a fusion protein to the chloroplast, and deletion of PAA1 results in decreased chloroplast copper levels and reduced activity of Cu/Zn superoxide dismutase and plastocyanin.…”
mentioning
confidence: 99%
“…2 Despite its physiological importance, excess copper is toxic for plants because of its potential participation in the Fenton reaction. To minimize the damage by excess copper and also respond to copper deficiency, higher plants have several strategies, including the regulation of copper uptake in root cells, 3 strict copper trafficking via P-type ATPases and copper chaperones [4][5][6][7][8][9] or regulation of the levels of copper proteins in response to a change in the metal availability. 10,11 In addition plants respond to copper deficiency by expressing the alternative iron proteins which complement the function of copper proteins.…”
mentioning
confidence: 99%